(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the effectiveness of the generative learning model in achievement and retentionInformation for fifth grade literary students in rhetoric. According to my research hypothesesThe two athens: - 1. There is no statistically significant difference at the significance level (0.05) between the mean scoresStudents of the experimental group who study according to the generative learning modelThe scores of students in the control group who study according to the usual methodachievement. 2 There is no statistically significant difference at the level of significance (0.05) between the mean scoresStudents of the experimental group who study according to the generative learning modelThe scores of students in the control group who study according to the usual methodInformation retention.